The Role of the successful managerial leaders in crises management (Journal of Accounting and Financial Studies ( JAFS ), 2014)
This research is a modest contribution to Put the finishing touches on therole of managerial leaders represented by static companies belonging to theministry of transport and communication/ [iraq] . the research has adopted thedescriptive. Analytical methodology and field study technique, using thequestionnaire as a tool for data collection [58] forms Nar, been distributed tothe research sample. The sample has been deliberately selected {generalmanager, as assistant general manager and heads of department}. Thequestionnaires and the main hypotheses of represented by the existence ofsignificant correlation and impact between successful managerial leadershipand crisis management using the software SPSS, were analyzed. Resultswere identical to the research hypotheses. It turns out that there is significantcorrelation and impact between successful managerial leadership and crisismanagement.